The Ifo DSGE Model for the German Economy - Nikolay Hristov (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
This paper estimates a medium-scale open economy DSGE model for Germany and therest of the Euro Area (REA). The parameter estimates indicate that there is a modestdegree of structural heterogeneity between Germany and the rest of the Euro Area. Inparticular, (i) the private sector in Germany tends to adjust its capital stock faster thanits counterpart in the REA, (ii) the innovations to government spending as well as thoseto the degree of competition in goods markets are relatively more volatile in Germanyand (iii) nominal prices and wages appear to be slightly more flexible in Germany thanin the REA. A comparison based on marginal likelihoods shows that the DSGE modelfits the observable macroeconomic time series similarly well as unrestricted BayesianVARs (BVARs) estimated on the same data set.
Keywords: C11; C51; E17; 330; DSGE model; German economy; monetary union; Bayesian estimation.